A discriminant analysis model of psychosocial predictors of problematic Internet use and cannabis use disorder in university students. (December 2021) - Akbari, Mehdi; Bahadori, Mohammad Hossein; Mohammadkhani, Shahram; Kolubinski, Daniel C.; Nikčević, Ana V.; Spada, Marcantonio M.
Highlights: A discriminant analysis model of psychosocial factors was devised to differentiate between PIU and CUD. Compared to the control group, the PIU group had higher scores on motor, attentional and non-planning impulsiveness; tolerance of frustration, emotional pain, and ambiguity; negative and positive metacognitions, need to control thoughts, and cognitive confidence; and RNT. Compared to the control group, the CUD group had lower scores on family and significant other support; and had higher scores on motor and non-planning impulsiveness; tolerance of frustration, emotional pain, and ambiguity; suppression; need to control thoughts; and RNT. Social support, tolerance of physical discomfort, reappraisal, and cognitive confidence play a significant role in discriminating PIU and CUD. The classification analysis results showed that 68.8% of the control group, 70.8% of the PIU group, and 81.3% of the CUD group were correctly classified in their respective groups based on the predictor variables. Abstract: Researchers have found similarities and differences between behavioral and drug addictions. The present study was designed to explore which of a series of psychosocial predictors of addictive behaviors could differentiate problematic Internet use (PIU) and Cannabis Use Disorder (CUD) in a sample of University students. A total of 144 participants (76 males, mean age = 23.03 years ± 2.83) were separated into three groups: those presenting with PIU (18 females, Mean age = 22.27 years), those presenting with CUD (22 female, Mean age = 22.73 years), and a control group (28 female, Mean age = 24.04 years). Participants completed the Internet Abusive Use Questionnaire (IAUQ), the Severity of Dependence Scale (SDS), the Multidimensional Scale of Perceived Social Support (MSPSS), the Barratt Impulsiveness Scale-11 (BIS-11), the Multidimensional Distress Tolerance Scale (MDTS), the Emotion Regulation Questionnaire (ERQ), the Metacognitions Questionnaire-30 (MCQ-30), and the Repetitive Thinking Questionnaire-10 (RTQ-10). The classification analysis results showed that 68.8% of the control group, 70.8% of the PIU group, and 81.3% of the CUD group were correctly classified in their respective groups. In addition, the results of the discriminant function analysis showed that there was a significant difference between members of the PIU and CUD groups in the degree of family support (0.45), significant other (0.33), tolerance of physical discomfort (0.30), reappraisal (0.42), and cognitive confidence (0.35). The findings provide evidence that specific psychosocial predictors can discriminate PIU from CUD.